Cations and dications of heavier group 14 elements in low oxidation states - Swamy, V. S. V. S. N.; Pal, Shiv; Khan, Shabana; Sen, Sakya S. (Dalton Transactions, 2015)
Cations and dications of heavier group 14 elements in their low oxidation state have received widespread attention in recent years. The journey started with the isolation of a series of cations of the composition [(C5Me5)E:](+) [E = Si-Pb], followed by the more recent isolation of a Ge(II) dication encapsulated within a cryptand, a carbodiphosphorane stabilized [GeCl](+) monocation with a two coordinate Ge atom, Si(II) cations and dications stabilized by N-heterocyclic carbenes (NHCs), which highlights the ongoing growth and interest in the chemistry of tetrel(II) cations. This is presumably because the central atom (E) in these compounds contains two or three unoccupied valence orbitals as well as holds a lone pair of electrons. Such an electronic description represents ambiphilicity, which is of great interest for catalysis. The successful synthesis of divalent group 14 cations requires new synthetic strategies based on the sterically demanding neutral or monoanionic ligands, utilization of counter anions, and solvents with low nucleophilicity in order to minimize the degree of interactions with the cations. An alternative approach for the realization of divalent cations of group 14 elements is their coordination to the transition metals. This synthetic approach was successfully applied for the isolation of a range of transition metal coordinated divalent cations of group 14 elements. Apart from arousing academic interest some of these cations have found application as activators in the Ziegler-Natta polymerization of alkenes.

Benz–amidinato stabilized a monomeric calcium Iodide and a lithium calciate(II) cluster featuring group 1 and group 2 elements - Yadav, Sandeep; Swamy, V. S. V. S. N.; Gonnade, Rajesh G.; Sen, Sakya S. (ChemistrySelect, 2016)
Soluble calcium halides reported so far are mostly dimeric in nature. The halides occupy the bridging position and thus provide additional coordination to the metal. We obtained a monomeric calcium iodide [{PhC(NiPr)(2)} CaI(thf)(3)] (1) from the reaction of [PhC(NiPr)(2)] Li with Cal(2) in THF. The compound has been stabilized by electronic donation and steric shielding from the amidinate ligand as well as coordination of three THF molecules. 1 does not show any propensity towards ligand exchange reaction. When the same reaction is carried out in diethyl ether instead of THF, it led to the formation of a Li calciate(II) cluster of composition L2Ca4I8Li4O (L= PhC(NiPr)(2)) (2) with an encapsulated O2+ in the middle of a tetrahedron spanned by four Ca2+ ions. 2 represents a metal-rich halide comprising of both alkali and alkaline earth metals which is quite unprecedented. Another notable aspect is that the amidinate ligand binds to the calcium atom in chelating bidentate mode in 1, whereas in 2 each N atom of the amidinate ligands binds to two Ca atoms leading to bridging bis-chelating coordination mode.

Facile access to a Ge(II) dication stabilized by isocyanides - Swamy, V. S. V. S. N.; Yadav, Sandeep; Pal, Shiv; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2016)
Herein, we introduce isocyanide as a ligand in main group chemistry and describe the facile isolation of a Ge(II) dication. The reaction of 2,6-dimethylphenylisocyanide with GeCl2 leads to the formation of a Ge(II) dication with two [GeCl3](-) molecules as counter anions. The dicationic Ge(II) center is bound to four isocyanide ligands and also holds a lone pair of electrons. DFT calculations reveal that the dication is stabilized only by sigma-donation from the four isocyanide ligands. Natural population analysis gives a charge of +0.74 on the Ge(II) center, indicating that the positive charge is shared by the isocyanide substituents.

C(sp(3))-F, C(sp(2))-F and C(sp(3))-H bond activation at silicon(II) centers - Swamy, V. S. V. S. N.; Parvin, Nasrina; Raj, K. Vipin; Sen, Sakya S. (Chemical Communication, 2017)
Silylene [PhC(NtBu)(2)SiN(SiMe3)(2)] (1) cleaves the C(sp(3))-H and C-F bonds of acetophenone and 1,1,1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C-F/H bond cleavage. The scope of C-F bond activation has further been extended with C6F6 and C6F5CF3.
Keywords: Boron triple bond; C-F Bond; Fluorinated Building-Block; H Activation; Ketones; N-heterocyclic carbenes; Oxodative Addition; Perfluorinated Arenes; Selective Activation; Transition-Metal Centers

Metal free mild and selective aldehyde cyanosilylation by a neutral penta-coordinate silicon compound - Swamy, V. S. V. S. N.; Bisai, Milan Kumar; Das, Tamal; Sen, Sakya S. (Chemical Communications, 2017)
This study demonstrates the preparation and structural characterization of a Si(IV) hydride (PhC(NtBu)(2)SiH(CH3)Cl) (1) and its use as a catalyst for the cyanosilylation of a variety of aldehydes. Compound 1 represents the first neutral penta-coordinate silicon(IV) species that catalyzes cyanosilylation of aldehydes under mild conditions.

Facile activation of Si-H bond by an electrophilic carbene - Swamy, V. S. V. S. N.; Kundu, Gargi; Sen, Sakya S. (Indian Chemical Society, 2018)
Herein, we have explored the chemistry of 1,3-bis(2,6-di-isopropylphenyl)-5,5-dimethy1-4,6-diketopyrimidinyl-2-ylidene (1) with various silanes under mild conditions. The oxidative addition of Si-H bond of phenylsilane with DAC 1 affords the compound 2, which is unambiguously characterized by muitinuclear NMR spectroscopy, elemental analysis, and X-ray single crystal diffraction studies. Interestingly, DAC 1 activates silicon hydride bond of chlorosilanes at room temperature and results in the corresponding silylation products.

Silylene induced cooperative B-H bond activation and unprecedented aldehyde C-H bond splitting with amidinate ring expansion - Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S.; Roesky, Herbert W. (Chemical Communications, 2019)
The addition of HBpin to PhC(NtBu)(2)SiN(SiMe3)(2) (1) results in the cleavage of the B-H bond in a cooperative fashion across the Si and amidinate-C sites. The reaction of 1 with benzaldehyde led to C-H bond activation with amidinate ring expansion leading to a five-membered heterocycle. In case of 4-fluorobenzaldehyde, a C-C bond coupling takes place leading to a dioxasilolane derivative as the major product.

Synthesis and reactivity of a hypersilylsilylene - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Das, Tamal; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Inorganic chemistry, 2019)
Stabilization of an amidinatosilylene with a bulky tris(trimethylsilyl)silyl substituent was realized with the preparation of PhC(NtBu)(2)Si{Si(SiMe3)(3)} (1) from PhC(NtBu)(2)SiHCl2 with K{Si(SiMe3)(3)} in more than 90% yield. The highly deshielded Si-29 NMR resonance (delta = 76.91 ppm) can be attributed to the absence of a pi-donating substituent. The molecular structure of 1 shows a trigonal-planar geometry around the Si-II center with a Si-II-Si-IV bond length of 2.4339(13) angstrom. A series of reactions of 1 with Me3NO, S, Se, and Te were performed. While siloxane derivatives (2 and 3) are obtained from reactions with Me3NO, silachalcogenones (4-6) are formed with other chalcogens. The presence of Si=E (E = S, Se, and Te) bonds in 4-6 have been confirmed by single crystal X-ray studies. Silaoxirane (7) formation was observed when 1 was treated with acetone, demonstrating the importance of the tris(trimethylsilyl)silyl group to kinetically and thermodynamically protect the silaoxirane derivative with less bulky substituents on the C atom.

Access to diverse germylenes and a six-membered dialane with a flexible beta-diketiminate - Pahar, Sanjukta; Swamy, V. S. V. S. N.; Das, Tamal; Gonnade, Rajesh G.; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2020)
A nacnac-based tridentate ligand containing a picolyl group (L) was employed to isolate chlorogermylene (1). The reaction of1with another equivalent of GeCl2 center dot dioxane surprisingly gave pyridylpyrrolide-based chlorogermylene (2)viaC-N bond cleavage and C-C coupling, while with AlCl3, it afforded a transmetalated product,4. The reaction of L with AlH3 center dot NMe2Et led to an unusual cyclohexane type six-membered dialane heterocycle (5).

Diverse reactivity of hypersilylsilylene with boranes and threecomponent reactions with aldehyde and HBpin - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2021)
The recently reported hypersilylsilylene PhC-(NtBu)(2)SiSi(SiMe3)(3) (1) reacts with BH3, 9-BBN, and PhBCl2 to yield the respective Lewis acid base adducts 2-4, respectively. Compound 4 undergoes isomerization to form a ring expansion product 5. The same silylene was found to initially form an adduct with HBpin (6) and subsequently isomerized to 7 via the rupture of the B-H bond of HBpin (7), where the hydride was bound to the carbon atom of the amidinate ligand and the Bpin unit was attached to the silicon center. Surprisingly, the reaction of 1 with HBcat results in PhC(NtBu)(2)Bcat (8). Subsequently, we have shown that HBcat forms the same product when it reacts with related silylene PhC(NtBu)(2)SiN(SiMe3)(3) (1'). With all of these reactions in hand, we ponder if silylene can activate two small molecules at one time. In this work, we delineate the three-component reactions of silylenes 1 and 1' with 4-fluorobenzaldehyde and HBpin, which afforded unusual coupling products, 9 and 10, respectively. Note that 9 and 10 were prepared from the cleavage of the B-H and C=O bonds by silylene in a single reaction and are the first structurally attested Si-C-O-B coupled products.